CHALLENGES OF SMART CONTRACTS IN THE AGE OF QUANTUM COMPUTING: AN ANALYSIS OF BLOCKCHAIN SECURITY - Macário, Luani Maria de Albuquerque; de Morais, Marielli Melo Soares (Seven Editora, 2024)
This study explores the interaction between smart contracts and quantum computing, mapping the main advantages, risks and vulnerabilities involved, in addition to analyzing the benefits of blockchain technology  and its insertion in the Brazilian legal world. Smart contracts are contracts programmed in a blockchain structure, which do not depend on human actions to be fulfilled. The use of blockchain in Law makes it possible to store encrypted data, making it difficult to violate and alter information. However, Brazilian legislation has not yet regulated the use of these techniques. The article addresses the main advantages of smart contracts, such as business autonomy, private data security, elimination of data manipulation, reliability, and agility. It proposes measures to ensure the robustness of smart contracts and blockchain in the face of the imminent advancement of quantum computing. The methodology used was a critical analysis, in which it is aimed at proposing measures that ensure the robustness of smart contracts and blockchain in the face of the imminent reality of quantum computing, through a literature review. The relevance of this work lies in the need to anticipate and mitigate potential threats, ensuring that these technological innovations deliver on their promise of security and reliability in an increasingly digitized society. It is understood that smart contracts represent an evolution in the automation of contracts, with the potential to change the way contractual relationships occur in the legal system, bringing new parameters to the law. DOI:https://doi.org/10.56238/sevened2024.037-019